العوامل الاجتماعية المؤدية للعنف المدرسي عند المراهق - ابتسام, دكاكن; أحمد, فريجة (Sciences de l'Homme et de la Société, 2017)
إن ظاهرة العنف ظاهرة قديمة جديدة، وهي تعبر عن مشكلة اجتماعية إنسانية تماس صورس وشككا ختتلف من جتتم آخرر صارتاف العااا،، والتقاليد، والأزمنة. والظرو الاجتماعية والإنسانية. والعنف المدسسي ما هر إلا صرسة من صرس العنف المنتشر في المجتم الكلي، إذ يماس من طر المجمرعة المدسسية وله عديد الأككا والاتجاها،، وهذا المقا سيهد صالدساسة والتحليل جملة العرامل الاجتماعية الدافعة صالمراهق إلى مماسسة العنف اارل المؤسسا، التعليمية. Abstract: The phenomenon of violence is a new old phenomenon, and it expresses a sosial and human problem that is practiced in images and forms differnt from one society to anothre according tocustoms, traditions, and times. Social and humanitarian conditions. School violence is only a form of violence in the whole society, practiced by the school group and has many forms and trends, this article will aim to study and analyze the social factors driving adolesents to violence within educational institutions.